The TexOx-1000 redshift survey of radio sources I: the TOOT00 region - Vardoulaki, E; Rawlings, S; Hill, G; Mauch, T; Inskip, K; Riley, J; Brand, K; Croft, S; Willott, C (2009)
We present optical spectroscopy, near-infrared (mostly K-band) and radio (151-MHz and 1.4-GHz) imaging of the first complete region (TOOT00) of the TexOx-1000 (TOOT) redshift survey of radio sources. The 0.0015-sr (~ 5 deg^2) TOOT00 region is selected from pointed observations of the Cambridge Low-Frequency Survey Telescope at 151 MHz at a flux density limit of ~= 100 mJy, ~ 5-times fainter than the 7C Redshift Survey (7CRS), and contains 47 radio sources. We have obtained 40 spectroscopic redshifts (~ 85% completeness). Adding redshifts estimated for the 7 other cases yields a median redshift z_med ~ 1.25. We find a significant population of objects with FRI-like radio structures at radio luminosities above both the low-redshift FRI/II break and the break in the radio luminosity function. The redshift distribution and sub-populations of TOOT00 are broadly consistent with extrapolations from the 7CRS/6CE/3CRR datasets underlying the SKADS Simulated Skies Semi-Empirical Extragalactic Database, S^3-SEX.